Integrating motivational interviewing with cognitive behavioural therapy for anxiety disorders, depression and co-morbid unhealthy lifestyle behaviours: a randomised controlled pilot trial. Issue 1 (19th January 2022) - Ghaderi, Ata; Rosendahl, Ingvar; Bohman, Benjamin
Abstract: Background: A substantial proportion of patients receiving cognitive behavioural therapy (CBT) do not achieve remission, and drop-out is considerable. Motivational interviewing (MI) may influence non-response and drop-out. Previous research shows that MI as a pre-treatment to CBT produces moderate effects compared with CBT alone. Studies integrating MI with CBT (MI-CBT) are scarce. Aims: To test the feasibility of MI-CBT in terms of therapist competence in MI and various participant measures, including recruitment and retention. In addition, separate preliminary evaluations were conducted, exploring the effects of CBT alone for anxiety disorders and depression, and of MI-CBT for anxiety disorders, depression and unhealthy lifestyle behaviours. Method: Using a randomised controlled parallel trial design, participants were recruited in routine psychiatric care and allocated to CBT alone or MI-CBT. Means in feasibility measures and within-condition Hedges' g effect sizes in treatment outcome measures were calculated. Authors were not blind to treatment allocation, while independent raters were blind. Results: Seventy-three patients were assessed for eligibility, and 49 were included. Participant perceptions of treatment credibility, expectancy for improvement, and working alliance were similar for both conditions. Overall, effect sizes were large across outcome measures for both conditions, including anxiety and depressive symptoms and functional impairment. However, therapists did not acquire sufficient competence in MI and the drop-out rate was high. Conclusions: MI-CBT proved feasible in some respects, but the present study did not support the progression to a randomised controlled trial designed to assess the effectiveness of MI-CBT. Additional pilot studies are needed.